The Kambārī in the Museum of the Frankincense Land, Salalah, Oman. (1st September 2019) - Weismann, Norbert; Dziamski, Piotr; Haar, Lilli
Abstract: This article examines the kambārī vessel now housed at the Museum of the Frankincense Land, Salalah, Oman, built for display in 1980. This sewn‐plank boat type, used for fishing and lightering in Dhofar, is discussed in the context of other similar vessels in Oman, South Yemen, and Somalia. As one of only five known surviving kambaris, a detailed account of this vessel's construction is given accompanied by an accurate pictoral record.